A novel transcriptional regulator, CdeR, modulates the type III secretion system via c-di-GMP signaling in Dickeya dadantii - Alaleh Ghasemi; Xiaochen Yuan; Ching-Hong Yang (Microbiology Spectrum)
ABSTRACT Dickeya dadantii is a bacterial pathogen that causes soft rot disease in many plant species worldwide, including temperate, subtropical, and tropical regions. This bacterium employs the type III secretion system (T3SS) to manipulate host immune responses. Although cyclic-di-GMP (c-di-GMP), a ubiquitous bacterial second messenger, negatively regulates the expression of T3SS genes in D. dadantii, the underlying mechanism remains unclear. In this study, we identified a potential transcriptional regulator, CdeR, which regulates the T3SS involving c-di-GMP. Through transposon mutagenesis, we discovered that deletion of cdeR in a gcpD mutant background restored T3SS gene expression. GcpD is a diguanylate cyclase responsible for c-di-GMP synthesis, and its deletion led to high T3SS gene expression due to low c-di-GMP. Further analysis revealed that, in the gcpD mutant background, CdeR regulates T3SS by manipulating intracellular c-di-GMP levels, involving another diguanylate cyclase, GcpL, whose expression is upregulated by CdeR. Additionally, we found that removing helical regions within the Helix-Turn-Helix DNA-binding domain of CdeR completely disrupted its regulation of the T3SS, underscoring the essential role of this domain in CdeR’s functional activity. This study is the first to identify CdeR as a potential transcriptional regulator involved in T3SS regulation. Our findings provide significant insights into the regulatory mechanisms of T3SS and highlight the complex interactions between bacterial second messengers and transcriptional regulators in pathogenic bacteria.IMPORTANCEBacterial pathogens, such as Dickeya dadantii, must adapt to diverse environmental and host conditions by utilizing intricate regulatory networks to control virulence. This study identifies CdeR, a novel transcriptional regulator, as a crucial factor in modulating the expression of the type III secretion system (T3SS), a key virulence mechanism. Importantly, we show that CdeR operates in a cyclic-di-GMP (c-di-GMP)-dependent manner, linking this second messenger to T3SS regulation in D. dadantii for the first time. Our findings reveal a sophisticated interaction between c-di-GMP signaling and transcriptional regulation, highlighting how these systems collectively drive bacterial virulence. This work advances our understanding of bacterial pathogenesis and opens new avenues for developing targeted strategies to mitigate soft rot disease in crops, potentially improving agricultural productivity and plant health.